An algorithm for generating uniform points on a cylindrical surface. (August 2020) - Zhu, Jiayi; Li, Hongjun
Abstract: The existing Poisson-disk sampling methods work well in traditional space, whatever two dimensional or three dimensional space. However, there are few methods on generating random points in non-Euclid space. For generating uniform points on the cylinder surface, we propose an algorithm which combines Poisson-Disk sampling algorithm with cylindrical distance constraints in this paper. Experiment results show that the quality of the point set generated by the proposed algorithm is better than that generated by the pseudo-random number method in both uniformity and stability.